Effect Of Coupling Agent On Mechanical Properties Of Composite From Kenaf And Recycled Polypropylene - M. R., Islam (2010)

(untitled)
This study shows the effect of using Maleated polypropylene (MAPP) as coupling agent on composites of RPP/kenaf fibre. Grinded fibre was compounded into recycled polypropylene with and without MAPP using a twin-screw compounder. The incorporated fibres in the composites were up to 50 wt%. The compounded samples were prepared into test specimens by injection moulder. The composites were characterized by tensile strength (TS), tensile modulus (TM), melt flow index (MFI). Incorporation of coupling agent had shown better result than that of without coupling agent to a certain level of fibre loading.